Igeza lensizwa as fashioned by ILanga le Theku - Ngwane, Simphiwe Blessing Mthokozelwa (University of the Witwatersrand, Johannesburg, 2023)
The objective of this study is to explore, analyse and interpret igeza lensizwa fashion inspired photographs on the back page of the first isiZulu-language lifestyle supplement called ILanga le Theku. These were photographs of street-casted young black men from around eThekwini that were being foregrounded as public scripts of youthful Zulu masculinities. Through a discursive approach to Critical Masculinities Studies, I interrogate how young Zulu men made situated decisions in the fashioning of their masculinities. The study engages other interlocutors that were involved in the fashioning of igeza lensizwa. These were the female-led editorial team, the mostly male photographers that street-casted and photographed young men, the young men that agreed and those that did not agree to be street-casted, and the female readers, as represented by the female persona. All these interlocutors had a hand in shaping the form of igeza lensizwa. The archive of the fashion inspired photographs of amageza ezinsizwa and their accompanying captions were approached as key sites where masculine representations were being articulated and contested. The study demonstrates how ILanga le Theku devised various literary techniques to cater for its two implied readers/audiences of igeza lensizwa. Through analysing these literary techniques, the study crafted two concepts to offer more context-based readings of Zulu masculinities as represented in ILanga le Theku. The study foregrounds a concept of igeza lensizwa as being comprised of ukuzithemba [self confidence] and ukuzizwa [self-regard]. The other concept is, thirst-trap which is achieved if the image of igeza lensizwa complies with ukuheha [to entice] and ukuchaza [to have an affect], in relation to the implied female audience. The study demonstrates how these two concepts offer insights on Zulu masculinities by engaging how young people eThekwini were changing dual gender systems norms and matters of desire. Moreover, the study shows how the section was also a site that challenged the myopic limits of homosocial desire with its limitation of masculine desire only incorporating interpersonal attractions. Furthermore, the study demonstrates that through shifts in spectatorship, facilitated by an auto-ethnographic queer lens as method, I inferred looking relations that, inter alia, explored how young men were asked to introspect, and confront masculine beauty.
Thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, In fulfilment of the requirements for the degree of Doctor of Philosophy. Department of African Literature, School of Literature, Language and Media, Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Igeza lensizwa; Zulu masculinities; Masculine representation; Queer lens; Thirst-trap; ILanga le Theku; Critical Masculinities Studies; SDG-4: Quality education